The perception of cooling roofs among professionals in Iran - Taheri, Mohammad Reza; A. Rahman, Nordin; Salleh, Elias (Faculty of Design & Architecture, Universiti Putra Malaysia, 2007)
A large amount of energy in Iran is currently being consumed for heating and cooling purposes in buildings. Since building rooftop surfaces absorb most of the solar radiation, green roofs are among the solutions recommended by scholars. This study utilizes a survey amongst a targeted sample population of 40 built environment professionals to determine their perception on the use of green roof for environmental cooling purposes. They believed that green roofs could improve the ecology and the biodiversity of an urban area. Green rooftops are also believed to have the capability to reduce air pollution and urban heat island, and help reduce solar radiation and energy consumption in Iranian cities. The best choices for implementation include flat asphalt, flat concrete, and flat tile roofs. The study recommends further study on developing a green rooftop policy for Iran that would improve the quality of life for people living in cities of Iran.